Associations Between Risk Perceptions and Cigarette, E-cigarette, and Dual-Product Use Among Canadian Adolescents. (March 2020) - Manzione, Lauren C; Shan, Lingpeng; Azagba, Sunday
Introduction: The popularity of e-cigarettes has increased significantly in recent years. E-cigarettes are perceived as less harmful than cigarettes, and both dual-use of cigarette and e-cigarette use is common among adolescents. This study assessed cigarette and e-cigarette risk perception and associations with dual-product use among Canadian adolescents. Methods: We used data from the 2016-2017 Canadian Student Tobacco, Alcohol, and Drugs Survey. Perceived risks of cigarette and e-cigarette use were classified into 4 categories: "high-risk perception, " "high-e-cigarette-risk and low-cigarette-risk perception, " "low-e-cigarette-risk and high-cigarette-risk perception, " and "low-risk perception." Adjusted odds ratios (aOR) were estimated from multinomial logistic regression. Results: Of the population, 92% perceived high risk from cigarettes, and 65% from e-cigarettes. Compared to students with low-risk perception, those with high-risk perception of both products had lower odds of dual-use (aOR: 0.21; 95% confidence interval [CI]: 0.15, 0.28), cigarette-only use (aOR: 0.33; 95% CI: 0.25, 0.45), and e-cigarette-only use (aOR: 0.64; 95% CI: 0.51, 0.79) relative to nonusers. Adolescents with high-e-cigarette and low-cigarette-risk perception had higher odds of e-cigarette-only use, relative to nonusers. Those with high-risk perception were more likely to be e-cigarette-only users relative to cigarette-only users. Conclusion: Results highlight that high perceived risk is associated with lower odds of use. However, those with a high-risk perception of both products had higher odds of e-cigarette use relative to cigarette-only users; as did those with high-e-cigarette and low-cigarette-risk perception, relative to nonusers. Future research should assess ways of communicating the risks of adolescent tobacco use.